Ultrasonic spot welded 6111-T4 aluminum alloy to galvanized high-strength low-alloy steel: Microstructure and mechanical properties. (5th January 2017) - Macwan, A.; Kumar, A.; Chen, D.L.
Abstract: Multi-material design of automotive structures for lightweighting solutions inevitably involves dissimilar joining of lightweight aluminum alloys with steels. Solid-state ultrasonic spot welding (USW) has recently received significant attention due to its high energy efficiency in comparison with conventional fusion welding techniques. In this study USW technique was used to join Al alloy 6111-T4 to galvanized high-strength low-alloy (HSLA) steel at different welding energy levels. During USW rapid interdiffusion of Zn and Al resulted in the formation of Al-Zn eutectoid/eutectic interface layer due to fast temperature rise and high strain rate. Part of this diffusion layer was squeezed out around the nugget edge in higher welding energy conditions, creating an additional brazing effect. The tensile lap shear load increased with increasing welding energy, reached a peak value, then decreased with a further increase in energy. Two major types of failure mode, namely interfacial failure and transverse-through-thickness (TTT) failure, were observed during tensile lap shear tests. The samples welded at 2000 J exhibited a longer fatigue life than those welded at a welding energy of 1000 J. During fatigue interfacial failure occurred at higher cyclic load levels, while TTT failure happened at lower cyclic load levels. Graphical abstract: Highlights: Rapid diffusion occurs between Al and Zn coating on HSLA steel during USW. A characteristic diffusion pattern forms at higher welding energy levels. Squeezed-out AlZn eutectic and Zn exhibit a brazing effect. Tensile lap shear strength is higher in Al-to-galvanized steel than Al-to-Al joints. Fatigue life is longer in the joint made at 2000 J than that made at 1000 J.